DECISION MAKING ANALYSIS OF AUTO-ID SYSTEM USING ANALYTICAL HIERARCHY PROCESS (AHP) AT PT. AKG - Rezananda Yulian Akbar; Muhammad Hisjam (Center for Study and Journal Management FTI UMI, 2021)
The increasingly competitive industrial competition makes companies from all sectors around the world change the system to be more efficient and effective. One of the efforts to improve the company is by implementing a Warehouse Management System (WMS). Lately, many large companies are implementing Auto-ID (automatic identification) technology to solve existing problems. The types of Auto-ID technology that are often used are barcode, RFID and QR code technology. PT AKG is a manufacturing company that produces and markets plastic finished materials to serve the needs of other companies has not yet implemented WMS, this causes human error due to the process still manual. This research proposed to find the best warehouse management system using the Analytical Hierarchy Process (AHP) method for PT. AKG. Alternative systems in this study are barcode, RFID, and QR code with the criteria used are cost, fuctionality, performance, and sustainability. Based on the results, the system chosen is the QR code with a score of 0.578084. QR codes can make it easier for operators and PPIC department staff to take notes and minimize recording errors. Recording that originally used Microsoft Excel and paper as a tool is no longer needed because operators only need to scan using a smartphone that is connected to the company's warehouse management system.